Overweight in schoolchildren and nutrient intake (2021)
Introduction: According to the World Health Organization (WHO), one of the most serious health problems of the 21st century is childhood obesity. In 2016, more than 400 million children and adolescents between the age of 5 and 19 were overweight or obese. The aim of this study is to evaluate the consumption, habits and dietary practices of schoolchildren who suffer from malnutrition due to overweight or obesity. Methods: descriptive, correlational and prospective study using a quantitative approach. The sample size was 82 girls and boys who met the inclusion criteria between 8 and 14 years of a public institution of basic education in Barranquilla. Results: schoolchildren of both sexes had a high prevalence of obesity, particularly in the female group (76.44%). A dietary interview using the frequency of food consumption method showed a moderate consumption of fruits and vegetables, as well as a high consumption of sugary drinks, fried foods, cookies and sweets, and a low intake of water. Regarding eating habits and practices, it was reported that a high percentage of schoolchildren receive diets and purchase cookies, ice cream, sugary drink or juices and salty snacks. Discussion: a a study revealed in 56 schoolchildren evaluated the prevalence of overweight of Spanish schoolchildren according to sex, thus showing a higher prevalence of overweight in girls (21.9%) than in boys, (10.1%) while the prevalence go obesity was higher in boys (24.5%) than in girls (9.7%). A systematic analysis reported in a population of children and adults from 1980 to 2013, finding a prevalence of overweight and obesity in boys (26.3% and 9.4%, respectively) and girls (27.3% and 8.3%). Our study presents excessive figures related to obesity mainly in schoolgirls (76.44%). Conclusion: Our data show a relationship between the prevalence of overweight and obesity and poor consumption and eating habits and practices.